Iron Intake and Hemoglobin Levels in Stunting in Adolescent - Addistyane Puristasari; Siti Nur Fatimah; Faisal Faisal (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Growth problem, such as stunting is still a major issue in the world. The prevalence of stunting in Indonesia increases throughout the years. Chronic undernutrition in adolescent with stunting, low socioeconomic, and education levels in a family can contribute to low iron intake. Low iron intake leads to low hemoglobin level. This study aimed to compare iron intake and hemoglobin level between stunting and non-stunting adolescent.Methods: This study was conducted to 59 respondents aged 11–14 years old from a Junior High School in Jatinangor, West Java from September to October 2014. Those respondents were divided into two groups: stunting and non-stunting group. This study was an analytic comparative study using cross-sectional method. Data were collected through body height measurement, hemoglobin level examination, and interviews of iron-containing food intake. The collected data were analyzed using t-test and Mann-Whitney U test.Results: Twenty eight of 59 subjects were stunting and 31 were normal. The mean of hemoglobin level was 12.95 (0.95) in stunting adolescent and 13.66 (1.35) in non-stunting adolescent. The mean iron intake was 23.9 (24.39) mg/day in stunting adolescent and 23 (22.6) mg/day in non-stunting adolescent. There was a difference of hemoglobin between those groups, but not in iron intake.Conclusions: Stunting adolescent has lower hemoglobin levels compared to non-stunting adolescent. There is no difference of iron intake levels between stunting and non-stunting adolescent. [AMJ.2016;3(2):175–80]DOI: 10.15850/amj.v3n2.782